1972
DOI: 10.1161/01.cir.46.4.640
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Infarct Size in Man and its Relation to Prognosis

Abstract: SUMMARYInfarct size was assessed quantitatively in 33 patients with acute myocardial infarction with a new technic based on analysis of serial serum creatine phosphokinase (CPK) changes to determine its relationship to prognosis. We have recently measured infarct size in the conscious dog with this method which takes into account CPK distribution space, fractional disappearance rate, proportion degraded in myocardium, and proportion released into the circulation, and we have validated the method by measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
141
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 687 publications
(146 citation statements)
references
References 14 publications
5
141
0
Order By: Relevance
“…Such quantitation of infarction could be of critical importance in determining patient prognosis and in guiding therapy. 20 It has been shown that CPK depletion is propor- farction in the heart at postmortem examination. Most important, it was also possible to predict the area and weight of infarction in the living animal.…”
Section: Discussionmentioning
confidence: 99%
“…Such quantitation of infarction could be of critical importance in determining patient prognosis and in guiding therapy. 20 It has been shown that CPK depletion is propor- farction in the heart at postmortem examination. Most important, it was also possible to predict the area and weight of infarction in the living animal.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, overexpression of HGF might enhance angiogenesis in myocardial infarction. Since the size of myocardial infarction correlates closely with mortality and residual impairment of function in survivors, 36 a therapy targeted at promoting collateral formation would decrease the size of chronic myocardial infarction. Indeed, the beneficial effect of HGF gene transfer was also reported by Ueda et al 37 They demonstrated that transfection of HGF gene into transplanted hearts resulted in the attenuation of reperfusion injury.…”
Section: Figure 3 Effect Of the Transfection Of Hgf Vector On The Vasmentioning
confidence: 99%
“…The incidence and prognosis of heart failure and ventricular arrhythmias after acute coronary occlusion are related to myocardial infarction (MI) size (1)(2)(3)(4). The transmural extent of MI has been shown to be related to probability of functional recovery after acute revascularization (5).…”
Section: Introductionmentioning
confidence: 99%